ENTREPRENEURSHIP THEORY - Rudianto, Y. Lilik (Program Doktor Ilmu Ekonomi, 2009)
The objective of this paper is to assess the basis of the entrepreneurial theories. It discusses the process of entrepreneurship, and models of entrepreneurship are also assessed. These are the simple Hollenbeck–Whitener model, Sanberg’s model, and the preliminary VCP model. Additionally, it explores the abilities, skills, aptitudes, and entrepreneurial competencies from a process perspective. The process of entrepreneurship can be illustrated as being central to the duties performed to maintain the progress of the economic sector. This process is supported by people who search for new and more efficient ways to achieve their business objectives. There is a belief concerning the creation of entrepreneurship that is focused on the inherent, personal characteristics of the entrepreneur. That it is not a new thing for entrepreneurs to display several universal characteristic and knowledge related to their community, and this makes them different from others. New venture performance (NVP) is a function of the characteristics of the entrepreneur (E), the structure of the industry in which the venture competes (IS), and its business strategy (S). Keywords: Process of entrepreneurship, entrepreneurial traits, new venture performance (NVP), value creation performance (VCP).